Digitalni prostor - Ciglič, Rok; Perko, Drago; Zorn, Matija (GIS v Sloveniji, 2014)
Digitalni prostor ('Digital Space') is the twelfth volume in the series GIS v Sloveniji (GIS in Slovenia). The goal of this volume is to present the wide variety of research findings on geographical information systems in Slovenia in recent years. Thanks to the development of technology and a wide selection of digital data, GIS users can explore digital space from several aspects. The volume clearly presents project results and research in areas such as geography, hydrology, protection against natural disasters, history, literary studies, regulation of traffic and mobility, agriculture, archaeology, remote sensing, and the energy industry. Readers will find new features regarding GIS applicability and learn about interesting findings in these areas.